(untitled) (Mutah Journal of Humanities and Social Sciences (MJHSS), 2024)
This study examines the impact of firm characteristics, namely size, leverage, profitability, and growth on the asset turnover ratio, which inversely measure the firm’s agency costs. Using data about non-financial firms listed on the Amman Stock Exchange, the results of the Generalized Method of Moments) GMM) estimator show that leverage, profitability, and growth are positively related to asset turnover, suggesting that firms with higher leverage ratios, profitable firms, and firms with higher investment opportunities experience lower agency costs compared to their counterparts. However, this study finds no evidence on the impact of firm size on asset turnover. Finally, this study finds that managers of Jordanian firms set a target level of agency costs and attempt to gradually adjust the agency cost level towards that target. Results of this study are of high importance for firms’ managers and policy makers as it sheds light on the important factors that affect the agency costs of these firms.